An Empirical Analysis of the Quality of Corporate Financial Disclosure. - Singhvi, Surendra S.; Desai, Harsha B. (The Accounting Review, 1971)
Abstract In a free enterprise system, variations in corporate disclosure practices are likely to result since corporations are managed by groups which have varying managerial philosophies and wide discretion in connection with disclosing information to the investing public. The quality of corporate disclosure influences to a great extent the quality of investment decisions made by investors. This study attempts to identify some of the characteristics of corporations in the U.S. which are associated with, and the probable implications of, the quality of corporate disclosure. Corporate disclosure of information can take several forms and the annual report to stockholders is a very important form of periodical corporate disclosure. This study demonstrates that the corporations which disclose inadequate information are likely to be small in size as measured by total assets, small in size as measured by number of stockholders, free from listing requirements, audited by a small accounting firm, less profitable as measured by rate of return, and less profitable as measured by earnings margin.